Analisis Nilai Tasawuf dalam Pembinaan Moral dan Mental Remaja di Indonesia - Elga Sepriana; Umi Nur Kholifah (Al-Kindi, 2025)
This study aims to analyze Sufi values ​​in the moral and mental development of adolescents in Indonesia as an effort to address various psychological challenges and moral crises in the modern era. Using a qualitative approach and a literature review, this study compiled various literature sources, such as Sufi books, scientific journals, and research findings related to adolescent moral education. Data collection was conducted through documentation techniques by reviewing relevant texts and scientific works. Data were then analyzed using content analysis methods to identify the main Sufi concepts that play a role in adolescent character formation. The results indicate that Sufi values, such as tazkiyatun nafs (self-control), muhasabah (introspection), patience, gratitude, and tawadhu' (respect for oneself), contribute significantly to strengthening adolescent morality, fostering self-awareness, and enhancing mental resilience in the face of social pressures and technological developments. This study confirms that the application of Sufi values ​​can be an effective alternative approach to developing the character of Indonesian adolescents in a more humanistic, transformative, and sustainable manner.